THE EFFECT OF PARENTS ATTENTION AND INTERESTS TO READ THE RESULTS OF LEARNING TO INDONESIAN LANGUAGE - YATI, TRI APRI (KALAM CENDEKIA PGSD KEBUMEN, 2013)
The purpose of this research was to determine the relationship between the attention of parents learning outcomes Indonesian language, the relationship between interest in reading the results of learning the Indonesian language, and the relationship between the attention of parents and interest in reading the results of learning Indonesian. This study used a correlational survey method with the quantitative approach and multiple regression analysis. Conclusions This study is there are significant effect between parental attention outcomes learning Indonesian results by 43,92%, the reading interests of the Indonesian language results by 34,22% and learning outcomes between the attention of parents and interest in the students' reading together the learning outcomes of the Indonesian language results by 78,15%. Keywords: parents attention, reading and interest.